2014
DOI: 10.11646/phytotaxa.172.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Musa ruiliensis (Musaceae, Section Musa), a new species from Yunnan, China

Abstract: A new species Musa ruiliensis, which occurs in Yunnan, China, is described based on morphological characters and molecular phylogeny. It belongs to Musa sect. Musa (former Rhodochlamys) and has close relationship with Musa chunii Häkkinen and Musa rubinea Häkkinen & C.H.Teo. A detailed description, chromosome cytology (2n = 2x = 22) and phylogenetic position are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…M. tongbiguanensis is a new species of Musa that we observed and described in Yunnan, China (Chen et al , 2008). The vernacular name of M. tongbiguanensis is ‘lubajiao’ (green banana); its main characteristics are large fruit and seeds (seeds are approximately two-fold larger than those of M. acuminata var.…”
Section: Discussionmentioning
confidence: 96%
“…M. tongbiguanensis is a new species of Musa that we observed and described in Yunnan, China (Chen et al , 2008). The vernacular name of M. tongbiguanensis is ‘lubajiao’ (green banana); its main characteristics are large fruit and seeds (seeds are approximately two-fold larger than those of M. acuminata var.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the study of Häkkinen & Väre () and the number of newly described Musa species since 2008 (e.g. Chen et al ., ; Dey et al ., ), we estimate the number of Musa species at c . 70 distinct entities.…”
Section: Methodsmentioning
confidence: 98%
“…Based on the study of H€ akkinen & V€ are (2008) and the number of newly described Musa species since 2008 (e.g. Chen et al, 2014;Dey et al, 2014), we estimate the number of Musa species at c. 70 distinct entities. In addition, based on the rather clear delimitation of most Musa acuminata subspecies in our phylogenetic analyses and the general, often arbitrary, delineation of natural lineages in species or subspecies (Hamilton & Reichard, 1992;Mayr, 2000), we decided to consider the different subspecies of Musa acuminata (and likewise also the subspecies of other Musa species) as different entities for both diversification rate methods.…”
Section: Musaceae Diversificationmentioning
confidence: 99%
“…Overall, classification of plants within the genus Musa is difficult even for skilled taxonomists, and new taxa have been reported mainly based on morphological characters [ 40 – 42 , 47 – 49 ]. This study demonstrated the feasibility of using high-throughput sequencing data, in association with biological information such as morphological characters, biogeographic history, and ecological differentiation for the delimitation of ESUs within the genus Musa .…”
Section: Discussionmentioning
confidence: 99%